Indeks Szeged dan Indeks Padmakar-Ivan pada Graf Nilpoten pada Gelanggang Bilangan Bulat Modulo Orde Prima Berpangkat - Muhammad Naoval Husni; I Gede Adhitya Wisnu Wardhana; Putu Kartika Dewi; I Nengah Suparta (Jurnal Matematika, Statistika dan Komputasi, 2024)
Recently, graphs have started to be used to represent a finite ring. Nikmehr and  Khojasteh in the article  defined the nilpotent graph of a ring . Denoted , is a graph with the set of vertices being all the elements in the ring  Two vertices  and  are adjacent if and only if  is nilpotent elements in the ring . Topological index is a field that discusses graph structure based on the degree of each vertex of a graph and the distance between vertices.  In this study, the author will gives the general formula of the Szeged index and Padmakar-Ivan index of the nilpotent graph graph of the modulo ring with prime power order. The result of this research is a general formula for the topological indices of nilpotent graphs of the integer modulo ring, called the Szeged index and the Padmakar-Ivan index.